2004
DOI: 10.4028/www.scientific.net/msf.461-464.375
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium Modified Aluminide by a Vapour Pack Cementation Process for Thermal Barrier Applications: Formation Mechanisms and Properties

Abstract: The main mechanism of degradation of thermal barrier systems is the spallation of the thermally grown oxide (TGO) formed at the ceramic/metallic sub-layer. Present trends are the use of a platinum modified nickel aluminide layer as metallic sub-layer. But the effect of few p.p.m. or few % at. of zirconium on the oxidation of hipped or cast nickel aluminide was also studied for higher temperature applications. It has been shown that the system ZrO 2 -Y 2 O 3 (8% mass.) EBPVD / cast NiAl(Zr) had at 1200°C a life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Additionally, prior work has been conducted on bond coatings with zirconium as the reactive element. Schumann et al and Naveos et al showed that zirconium segregated to the oxide grain boundaries, possibly resulting in reduced aluminum diffusion into the oxide scale [13,14]. Another reported benefit is that reactive elements, including zirconium, interact with deleterious tramp elements such as sulfur that contaminate the coating-oxide interface.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, prior work has been conducted on bond coatings with zirconium as the reactive element. Schumann et al and Naveos et al showed that zirconium segregated to the oxide grain boundaries, possibly resulting in reduced aluminum diffusion into the oxide scale [13,14]. Another reported benefit is that reactive elements, including zirconium, interact with deleterious tramp elements such as sulfur that contaminate the coating-oxide interface.…”
Section: Discussionmentioning
confidence: 99%
“…С этой ЭЛЕКТРОННО-ЛУЧЕВЫЕ ПРОЦЕССЫ целью связующий слой NiAl дополнительно легируют введением небольшого количества (от 0,01 до 1 мас. %) различных активных к кислороду химических элементов, например Y, Zr, Ce, La, Hf, Dy [8][9][10], которые позволяют замедлить скорости роста слоя окалины Al 2 O 3 на поверхности NiAl, а также повысить адгезию слоя окалины. Позитивный эффект от введения указанных активных элементов (АЭ) связывают прежде всего с образованием «клиновидных» выделений на границе раздела окалины и NiAl, которые увеличивают сцепление слоя окалины с металлом, формированием слоя окалины с более совершенной структурой, а также с подавлением роста пустот/пор на межфазной границе и уменьшению «вспучивания» (rumpling) слоя окалины [11][12][13][14].…”
Section: к л ю ч е в ы е с л о в а : конденсационные градиентные термunclassified
“…Two other solutions can be considered in order to improve the aluminide mechanical properties: by modifying their microstructure using an innovative elaboration process [241][242][243], or by applying the intermetallic compounds directly on a metal or alloy surface [33,[244][245][246][247][248][249][250][251].…”
Section: Recent Developments In Alumina-forming Materials: Intermetalmentioning
confidence: 99%